Clinical observation of a prurigo nodularis in a HIV-positive patient - E. N. Efanova; Yu. E. Rusak; E. A. Vasileva (Лечащий Врач)
The human immunodeficiency virus (HIV) is a globally spreading virus that represents one of the most serious social and health problems. The epidemic situation of HIV (human immunodeficiency virus) infection in the world and, in particular, in the Russian Federation remains tense. In HIV-positive patients, specific lesions of the skin and mucous membranes are often noted. Skin processes in HIV-positive patients are usually atypical, have a torpid course, may occur in unusual age groups and are extremely difficult to respond to standard treatment. Lesions of the skin and mucous membranes in HIV-infected can be divided into several groups: allergic reactions, infectious, paraneoplastic processes and dermatoses with unknown pathogenesis. In the modern literature, the issue of the group of «dermatoses with an unclear pathogenesis» against the background of HIV infection, in particular about prurigo, is insufficiently illuminated. In the described clinical case, an HIV-positive patient with a rare manifestation of nodular prurigo is presented. The history of the issue, etiology, clinical manifestations, and treatment methods are covered. The presented case illustrates the manifestation of prurigo against the background of systemic causes (HIV infection) and initiation of highly active antiretroviral therapy without a previous atopic history. Contrary to the literature data, the CD4+ count in a patient with prurigo was more than 200 cells/μL, although pruritus is known to be a dermatoses with a low CD4+ cell count. The role of the immunodeficiency state in the pathogenesis of prurigo remains unclear. Perhaps, in this case, the development of dermatosis is provoked by a direct viral effect or the toxic effect of antiretroviral drugs. An interesting fact is the rapid positive response of the skin process to traditional therapy.